2016
DOI: 10.1007/s00401-016-1566-9
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of the genetic impact of rare variants in SORL1 in European early-onset Alzheimer’s disease

Abstract: The sortilin-related receptor 1 (SORL1) gene has been associated with increased risk for Alzheimer’s disease (AD). Rare genetic variants in the SORL1 gene have also been implicated in autosomal dominant early-onset AD (EOAD). Here we report a large-scale investigation of the contribution of genetic variability in SORL1 to EOAD in a European EOAD cohort. We performed massive parallel amplicon-based re-sequencing of the full coding region of SORL1 in 1255 EOAD patients and 1938 age- and origin-matched control in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 58 publications
(75 reference statements)
7
108
0
Order By: Relevance
“…In contrast to other hits from gene-wide association studies, which typically confer a small increase in AD risk, SORL1 variants have been found that confer a five-fold risk (Vardarajan et al, 2015; Verheijen et al, 2016), on par with APOE4 carriers. More importantly, recent studies suggest that rare SORL1 mutations are actually causal mutations (Pottier et al, 2012; Vardarajan et al, 2015), akin to the autosomal-dominant mutations in APP or PSEN s (Holstege et al, 2017).…”
Section: Endosomal Traffic Jams Can Occur As An Upstream Eventmentioning
confidence: 68%
“…In contrast to other hits from gene-wide association studies, which typically confer a small increase in AD risk, SORL1 variants have been found that confer a five-fold risk (Vardarajan et al, 2015; Verheijen et al, 2016), on par with APOE4 carriers. More importantly, recent studies suggest that rare SORL1 mutations are actually causal mutations (Pottier et al, 2012; Vardarajan et al, 2015), akin to the autosomal-dominant mutations in APP or PSEN s (Holstege et al, 2017).…”
Section: Endosomal Traffic Jams Can Occur As An Upstream Eventmentioning
confidence: 68%
“…SORL1 , was initially identified as a risk-factor in a case-control association-study [23], but has more recently been implicated in familial early-onset as well as late-onset AD [8, 16, 20, 21, 25, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…The variant was not detected in any other subject in the Amsterdam Dementia cohort. One study detected the variant in a 63-year-old healthy female (control group n  = 1938, MAF <0.001) [26], and the ExAC database reports only one heterozygous carrier of this variant (MAF <0.00001). The variant locus is at a highly conserved glycosylation site in the VPS10 domain of SORL1 (Fig.…”
Section: Resultsmentioning
confidence: 99%